2017
DOI: 10.1111/jam.13402
|View full text |Cite
|
Sign up to set email alerts
|

Laundry hygiene-how to get more than clean

Abstract: Summary Although laundering should mainly remove stains and dirt from used and worn textiles, the elimination of microbial contamination is an important aim of the laundry process as well. While industrial and institutional laundering employs standardized processes using high temperatures (i.e. 60°C and above) and bleaching agents to ensure a sufficient hygienic reconditioning of textiles, domestic laundering processes are less defined and not always led by purposeful aims. The strive for energy efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 44 publications
3
57
0
Order By: Relevance
“…For nearly all tested microbial strains, the LR at 30 °C and 40 °C were very similar, independent from the use of AOB or an increased main wash duration. This confirms the findings of studies using a domestic washing machine and T. mentagrophytes as a fungal test strain (Amichai et al, ; Bloomfield et al, ; Bockmühl, , ; Honisch et al, , ).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…For nearly all tested microbial strains, the LR at 30 °C and 40 °C were very similar, independent from the use of AOB or an increased main wash duration. This confirms the findings of studies using a domestic washing machine and T. mentagrophytes as a fungal test strain (Amichai et al, ; Bloomfield et al, ; Bockmühl, , ; Honisch et al, , ).…”
Section: Resultssupporting
confidence: 87%
“…While there was no cross‐contamination detectable when AOB was used, a significant transfer of microbial cells could be observed with the bleach‐free detergents at temperatures lower than 30 °C, and—for shorter durations—also at 40°C. This preventive effect of AOB‐containing detergents has previously been shown in several other studies dealing with domestic laundering processes (Arild et al, ; Bockmühl, ; Honisch et al, , ). Furthermore, it could be shown that not only the addition of AOB detergents but also higher washing temperatures (e.g., 60 °C) might prevent cross‐contamination.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The cleaning efficiency of a washing machine is depending on the mechanical circulation of the washing drum, the flooding of the fabric with water and detergents, as well as an appropriate washing time and water temperature [3][4][5]. Mainly for environmental reasons, the washing process has been adapted to sustain energy in order to conserve resources and reduce costs [6]. Sustainable washing trends include washing at lower temperatures, a reduced water consumption and an increased use of bleach-free liquid detergent [7].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms could be a potential reservoir for pathogens and might detach during the washing process and recontaminate the laundry. In this regard it can be assumed that the washing process may cause a shift in the microbial community on textiles form primary contaminants (skin bacteria) to secondary contaminants (biofilm-associated environmental bacteria) and that the water itself can also be a source for recontamination and contribute to secondary contamination [11].…”
Section: Discussionmentioning
confidence: 99%